Evaluation of beauty training programs in regional work training center of East Jakarta using the goal free evaluation model - Nely Suroyya Martalena; Dwi Atmanto; Jenny Sista Siregar (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2019)
This study aims to determine the impact of the beauty training program in PPKD of East Jakarta on students. The impact can be seen based on three criteria, namely positive impacts according to program objectives, positive impacts outside the program objectives (side effects), and negative impacts outside the program objectives. The research method used in this study is an evaluative study using the Goal Free Evaluation model. The research subjects consisted of: managers, instructors, and beauty training participants in PPKD of East Jakarta . Data was collected using observation, interviews, and documentation. The results showed that (1) the positive impact according to the program objectives was felt by almost all training participants, namely they could increase their knowledge and skills in the field of beauty and were ready to enter the workforce, (2) a positive impact outside the program objectives freelance work as a makeup artist, having confidence in work, and daring to open a business in the field of beauty, and (3) negative impacts outside the program's objectives felt by a small number of training participants who were less serious and less focused on training that they could not accept the material taught so that they are not ready to enter the workforce.